Weed species in tomato production and their role as alternate hosts of Tomato spotted wilt virus and its vector Frankliniella occidentalis. (13th April 2016) - Macharia, I.; Backhouse, D.; Wu, S.‐B.; Ateka, E.M.
Abstract: Tomato spotted wilt virus (TSWV) is an important plant virus that infects a wide range of hosts including weeds making its management difficult. A survey was undertaken to establish the occurrence of weed species in tomato production systems in Kenya and their role as hosts of TSWV and its vectors. Selected weed species were further evaluated for their reaction to TSWV, transmission efficiency by Frankliniella occidentalis and ability to support thrips reproduction. Of the 43 weed species identified in the field, 29 species had been reported as hosts of TSWV, two were non‐hosts and 11 had no record of their status. Among the more common species, Amaranthus hybridus, Solanum nigrum, Tagetes minuta and Datura stramonium were susceptible to the virus and supported high levels of thrips reproduction. The TSWV could not be transmitted to Galinsoga parviflora and Sonchus oleraceus by F. occidentalis despite them being highly susceptible in mechanical transmission tests. There was a significant correlation between feeding damage and number of larvae of F. occidentalis on different weeds. Occurrence of weeds that support thrips reproduction and are good hosts of TSWV is a clear indicator of their role in epidemiology and the importance of their management for disease control.